고온환경에서 돼지의 혈액 내 전해질 및 혈액학적 성분의 변화 - 김기현; 김광식; 김조은; 설국환; 홍준기; 정영훈; 박준철; 김영화; Ki Hyun Kim; Kwang Sik Kim; Jo Eun Kim; Kuk-Hwan Seol; et al. (농업생명과학연구, 2015)
본 연구는 고온 환경에서 Yorkshire 품종의 혈액 내 전해질과 혈액학적 성분의 변화를 조사하기 위하여 실시하였다. 73 일령(BW 40.6±1.4 kg)의 Yorkshire종 10두를 공시하여 개별 pen에 1두씩 배치하였다. 시험기간은 한국에서 폭염이 시작되는 2013년 7월 24일부터 동년 9월 4일까지 6주간 실시하였다. 시험기간 중 평균온도가 가장 높은 시기는 시험 3주차(28.6℃)였으며, 최고온도는 시험 4주(32.1℃)에 관찰되었다. 일당증체량은 온도가 가장 높았던 시험 3주차부터 감소하는 경향으로 나타났다. 혈청 내 pH와 삼투압은 시험기간 동안 유의적인 변화가 관찰되지 않았다. 나트륨이온 (P<0.01)과 염소이온(P<0.05)의 농도는 시험 6주에 유의적으로 증가하였다. 일반혈액검사 분석 결과에서 혈액 내 호중구(P<0.05)와 단핵구(P=0.057)의 수준은 시험 6주에 증가하고, 헤모글로빈과 평균 적혈구 혈색소 농도는 시험 4주와 6주에 감소하는 것으로 관찰되었다(P<0.05). 혈액생화학 분석에서는 총 콜레스테롤(P<0.01), 총 단백질(P<0.001)과 혈중 요소태 질소(P<0.01)의 농도가 4주와 6주에 높아지는 것으로 관찰되었으며, glucose 농도는 6주에 유의적으로 낮아졌다(P<0.05). 본 연구의 결과는 한국의 여름철 폭염기간 동안 돼지의 체내에서 생리생화학적, 혈액학적 변화가 어떻게 변하는지에 대한 기초정보를 제시하며, 이러한 정보는 혹서기 고온 스트레스로 인한 돼지 생산성저하 방지 기술을 개발하는 데에 기초자료로 활용될 수 있을 것으로 사료된다. This study was performed to investigate the changes of serum electrolytes and hematological profiles in Yorkshire at a high ambient temperature. A total of 10 Yorkshires (73 days old; 40.6±1.4 BW kg) were housed in individual pens and were reared under the environment of typical summer climate in Korea (from 24 July to 4 September, 2013). Growth performance was determined every week and blood samples were collected every second weeks from the jugular vein. The average temperature was the highest at third week (28.6℃), and the maximum temperature (32.1℃) was observed in fourth week of entire study period. Growth performance was decreased by heat stress after the first 3 week. Although the serum concentration of sodium (P<0.01) and chloride (P<0.05) ions were significantly increased at 6 week, serum pH and osmolality did not be affected by high temperature. Neutrophil (NE, P<0.05) and monocyte (MO, P=0.057) levels in blood were increased at 6 week. Hemoglobin (Hb, P<0.05) and mean corpuscular hemoglobin concentration (MCHC, P<0.001) were decreased at 4 and 6 week. Serum total cholesterol (P<0.01), total protein (P<0.001) and blood urea nitrogen (P<0.01) were significantly increased at 4 and 6 week, but serum glucose (P<0.05) concentration was significantly decreased at 6 week. This study certified that the physiological, biochemical, and hematological changes in pig take place at summer season in Korea. The present study’s results can be utilized as base line data for development of stress reduction techniques in pork industry.